PENGEMBANGAN MODEL KEPEMIMPINAN BIROKRASI DI INDONESIA - Awang Anwaruddin1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
The issue of bureaucratic reform has been blown up since the beginning of PresidentYudoyono‘s government. However, there hasn’t been a grand strategy formulated toimplement the reform since then. Consequently, several experts sue different concepts onnthe reform. In the perspective of the reform, this paper attempts at analyzing the models of bureaucratic leadership in Indonesia, and proposes a new model to be implemented.